2007
DOI: 10.1016/j.schres.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying incoherence in speech: An automated methodology and novel application to schizophrenia

Abstract: Incoherent discourse, with a disjointed flow of ideas, is a cardinal symptom in several psychiatric and neurological conditions. However, measuring incoherence has often been complex and subjective. We sought to validate an objective, intrinsically reliable, computational approach to quantifying speech incoherence. Patients with schizophrenia and healthy control volunteers were administered a variety of language tasks. The speech generated was transcribed and the coherence computed using Latent Semantic Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
313
4
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 283 publications
(334 citation statements)
references
References 25 publications
13
313
4
4
Order By: Relevance
“…A fourth limitation of this study is that participants tended to have been ill for long periods, and findings may not reflect word use in individuals with shorter durations of psychosis. To address these limitations, In the future, researchers should also seek to integrate lexical analysis with other types of speech instruments, such as latent semantic analysis and discourse incoherence measures, both of which have shown promise for investigating speech across the schizophrenia-spectrum (Docherty, 2012;Elvevag et al, 2007;Minor and Cohen, 2010;Minor and Cohen, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A fourth limitation of this study is that participants tended to have been ill for long periods, and findings may not reflect word use in individuals with shorter durations of psychosis. To address these limitations, In the future, researchers should also seek to integrate lexical analysis with other types of speech instruments, such as latent semantic analysis and discourse incoherence measures, both of which have shown promise for investigating speech across the schizophrenia-spectrum (Docherty, 2012;Elvevag et al, 2007;Minor and Cohen, 2010;Minor and Cohen, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Computational approaches have been applied to phenomena in Management, Sociology, Marketing, Health, and other disciplines -for example, in literature indexing (Foltz, 1995), evaluation of medical interventions and diagnoses (Elvevåg et al, 2007;Al Qenaei, 2009), and language-based communication (Dong, 2005). Still, these applications were restricted to one analysis approach in isolation, leading to a gap in knowledge about the similarities and differences in the examination of data between different analytical techniques.…”
Section: A U T H O R C O P Ymentioning
confidence: 99%
“…In order to establish an even better comparison and analyze further, we examined speech samples generated in response to the question "What activities do people generally do during the course of the day? ", (from Elvevåg et al, 2007) from a healthy participant (Sample 2), and three patients with schizophrenia (Samples 3 to 5). The responses were rated by two human raters for coherence (a score of 1 = very coherence versus 7 = very incoherent) and tangentiality (a score of 1 = very incisively related to question versus 7 = completely unrelated to question).…”
Section: 3b Transition Entropymentioning
confidence: 99%
“…Indeed, such studies -using Latent Semantic Analysis (LSA) which models and matches discourse content (Landauer and Dumais, 1997;Landauer et al, 2007) -have demonstrated that it is possible to evaluate patients with schizophrenia based on open-ended verbalizations. These automatically derived language scores have distinguished patients from controls accurately (and patients from other patients, and also from their family members), using both large discourse samples as well as responses consisting of only a few words (Elvevåg et al, 2007(Elvevåg et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%